Inside Saatchi & Saatchi - Clayton, Jennifer; Films for the Humanities & Sciences ([Princeton, NJ : Films for the Humanities & Sciences, 2005)
Can Saatchi & Saatchi turn Sagatiba cachaça, a sugarcane liquor popular in Brazil, into a globally recognized brand? This program tracks the Sagatiba launch from start to finish -- and in the process reveals the inner workings of an ad agency whose name is synonymous with success. Footage of key agency players brainstorming, running client meetings, producing commercials, and more illustrates how the iconic Jesus statue in Rio became the model for a cool young lookalike who stands in as the living image of the'Pure Spirit of Brazil.'
Title from title screen
Executive producer, Bill Grist
Narrator: Robert Lindsay
DVD format
Keywords: Saatchi & Saatchi; Advertising -- Alcoholic beverages -- Case studies; Alcoholic beverage industry -- Brazil -- Case studies